AnthWest, occurrence records for wool carder bees of the genus Anthidium (Hymenoptera, Megachilidae, Anthidiini) in the Western Hemisphere - Terry Griswold (ZooKeys, 2014)
This paper describes AnthWest, a large dataset that represents one of the outcomes of a comprehensive, broadly comparative study on the diversity, biology, biogeography, and evolution of Anthidium Fabricius in the Western Hemisphere. In this dataset a total of 22,648 adult occurrence records comprising 9657 unique events are documented for 92 species of Anthidium, including the invasive range of two introduced species from Eurasia, A. oblongatum (Illiger) and A. manicatum (Linnaeus). The geospatial coverage of the dataset extends from northern Canada and Alaska to southern Argentina, and from below sea level in Death Valley, California, USA, to 4700 m a.s.l. in Tucumán, Argentina. The majority of records in the dataset correspond to information recorded from individual specimens examined by the authors during this project and deposited in 60 biodiversity collections located in Africa, Europe, North and South America. A fraction (4.8%) of the occurrence records were taken from the literature, largely California records from a taxonomic treatment with some additional records for the two introduced species. The temporal scale of the dataset represents collection events recorded between 1886 and 2012. The dataset was developed employing SQL server 2008 r2. For each specimen, the following information is generally provided: scientific name including identification qualifier when species status is uncertain (e.g. “Questionable Determination” for 0.4% of the specimens), sex, temporal and geospatial details, coordinates, data collector, host plants, associated organisms, name of identifier, historic identification, historic identifier, taxonomic value (i.e., type specimen, voucher, etc.), and repository. For a small portion of the database records, bees associated with threatened or endangered plants (~ 0.08% of total records) as well as specimens collected as part of unpublished biological inventories (~17%), georeferencing is presented only to nearest degree and the information on floral host, locality, elevation, month, and day has been withheld. This database can potentially be used in species distribution and niche modeling studies, as well as in assessments of pollinator status and pollination services. For native pollinators, this large dataset of occurrence records is the first to be simultaneously developed during a species-level systematic study.